Chemotherapy-free treatment in patients with follicular lymphoma. Issue 2 (April 2014) - Sarkozy, Clémentine; Salles, Gilles; Bachy, Emmanuel
<x xml:space="preserve">Abstract</x> The outcome of patients with follicular lymphoma (FL) has improved over the last two decades through the introduction of anti-CD20 monoclonal antibodies, usually used in combination with chemotherapy. However, patients with FL still experience multiple relapses, requiring several lines of treatment. Early toxicity of chemotherapy is a significant concern and as the life expectancy of patients with FL is increasing, late toxicities become an increasingly important concern. Progress made in understanding the biology of FL, especially dysregulation of intracellular pathways and immunological antitumor responses, recently allowed for the development of innovative chemo-free therapeutic approaches. In this report, different options such as new anti-CD20 antibodies, antibodies targeting other cell surface antigens, bi-specific antibodies, immunomodulation, idiotype vaccine and other targeted therapies are presented. The article also highlights how, although promising in early phase studies, the cost–effectiveness of new agents will have to be justified in Phase III trials. Furthermore, chemo-free regimen might not mean toxicity-free treatment and monitoring of early and late toxicities is required.